2020
DOI: 10.1007/s00426-020-01316-1
|View full text |Cite
|
Sign up to set email alerts
|

Lower limb peripersonal space and the desire to amputate a leg

Abstract: Body integrity identity disorder (BIID) is a rare condition defined by a persistent desire to amputate or paralyze a healthy limb (usually one or both of the legs). This desire arises from experiencing a mismatch between the internal body model and the actual physical/functional boundaries of the body. People with BIID show an abnormal physiological response to stimuli approaching the affected (unwanted) but not the unaffected leg, which might suggest a retracted peripersonal space (PPS: a multisensory integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…This sample size is higher than in previously published behavioural studies on BID (e.g. Aoyama et al, 2012;Stone et al, 2019bStone et al, , 2020b, and was constrained by the rareness of BID. Participants were recruited from several European countries through online forums, personal contacts, and word of mouth.…”
Section: Participantsmentioning
confidence: 94%
See 1 more Smart Citation
“…This sample size is higher than in previously published behavioural studies on BID (e.g. Aoyama et al, 2012;Stone et al, 2019bStone et al, , 2020b, and was constrained by the rareness of BID. Participants were recruited from several European countries through online forums, personal contacts, and word of mouth.…”
Section: Participantsmentioning
confidence: 94%
“…Along these lines, several behavioural investigations showed differential effects between the affected and unaffected limb in body-related unisensory and/or multisensory processing by showing, for example, altered temporo-spatial processing of tactile stimuli (Aoyama et al, 2012), or altered reactions to pain, pain anticipation (Brang et al, 2008;Romano et al, 2015), and top-down modulation of pain. On the other hand, recent empirical studies suggested normal implicit and explicit judgements about body size and shape, independent of what modality their judgement was based on, a normal peripersonal space representation (Stone et al, 2020b), and no alterations in a mental rotation paradigm for body parts (Stone et al, 2019a).…”
Section: Introductionmentioning
confidence: 98%
“…We chose to focus on the lower body (including the feet) as we noted before that research indicates that lower-body stimuli may contribute to full-body PPS. The PPS relates the overall body to the objects surrounding us (Serino et al, 2015;Stone et al, 2017Stone et al, , 2020, as well as our body-ownership (Grivaz et al, 2017). As such it is directly relevant for actions in immersive environments where we need to react to or directly interact with objects around us.…”
Section: Problem Space and Approachmentioning
confidence: 99%
“…As research indicates that lower-body feedback contributes to full-body awareness and embodiment (Stone et al, 2017(Stone et al, , 2020, we assume that feet-based cues can be used to adjust users' navigation behaviour. During real-world movement the whole body is used instead of just specific body parts, such as the hands in case of selection and manipulation tasks.…”
Section: Potential Effects On Interactionmentioning
confidence: 99%
“…Specifically, in the Unfair TLCG (U-TLCG), a win for participants was always associated with the smallest monetary sum, while pickers always won the highest monetary rewards. This bias was motivated by the expected age of individuals with BID (whose mean age ranged from 43.1 to 49.6 years, in studies on BID) [34,38,[40][41][42][49][50][51][52][53][54] compared to previous TLCG experiments (mean age between 23.1 and 26.7 years) [41][42][43][44][45]. Most participants in previous TLCG studies were students, who, being generally unemployed, may have been tempted to lie even for small monetary rewards.…”
Section: Introductionmentioning
confidence: 99%